Anti-adenoviral Artificial MicroRNAs Expressed from AAV9 Vectors Inhibit Human Adenovirus Infection in Immunosuppressed Syrian Hamsters - Katrin Schaar; Anja Geisler; Milena Kraus; Sandra Pinkert; Markian Pryshliak; Jacqueline F. Spencer; Ann E. Tollefson; Baoling Ying; Jens Kurreck; William S. Wold; Robert Klopfleisch; Karoly Toth; et al. (Elsevier, 2017)
Infections of immunocompromised patients with human adenoviruses (hAd) can develop into life-threatening conditions, whereas drugs with anti-adenoviral efficiency are not clinically approved and have limited efficacy. Small double-stranded RNAs that induce RNAi represent a new class of promising anti-adenoviral therapeutics. However, as yet, their efficiency to treat hAd5 infections has only been investigated in vitro. In this study, we analyzed artificial microRNAs (amiRs) delivered by self-complementary adeno-associated virus (scAAV) vectors for treatment of hAd5 infections in immunosuppressed Syrian hamsters. In vitro evaluation of amiRs targeting the E1A, pTP, IVa2, and hexon genes of hAd5 revealed that two scAAV vectors containing three copies of amiR-pTP and three copies of amiR-E1A, or six copies of amiR-pTP, efficiently inhibited hAd5 replication and improved the viability of hAd5-infected cells. Prophylactic application of amiR-pTP/amiR-E1A- and amiR-pTP-expressing scAAV9 vectors, respectively, to immunosuppressed Syrian hamsters resulted in the reduction of hAd5 levels in the liver of up to two orders of magnitude and in reduction of liver damage. Concomitant application of the vectors also resulted in a decrease of hepatic hAd5 infection. No side effects were observed. These data demonstrate anti-adenoviral RNAi as a promising new approach to combat hAd5 infection. Keywords: adenovirus infection, RNA interference, antiviral therapy, AAV vector